Increasing Sales Omzet of Plant Waste Based Home Industry Through Product Development and Marketing (Indonesian Journal of Devotion and Empowerment, 2022)
The problems of household crafts (home industry) in general are production, human resources and marketing. Brongkol Craft, a business group of women in Tabaggunung Hamlet, Brongkol Village, Jambu District, Semarang Regency, Central Java, which was founded in 2019, also experienced the same thing. The pandemic condition worsened the business condition. This service aims to increase Brongkol Craft sales turnover through the development and improvement of production, HR and marketing aspects. Problem-solving methods are generally carried out in a participatory manner, training, mentoring, monitoring, and evaluation at Brongkol Craft partner locations. Training is implemented through tutorials, discussions, demonstrations, and practices. Brongkol Craft Partners actively participate in all activities in implementing this activity. Each activity stage is monitored and evaluated on participation, knowledge, skills in implementing science and technology transfer, attitudes, and outcomes in each activity. Community service results in the development of Brongkol craft products, namely waste-based tote bags, pillowcases, tablecloths, hats and other accessories. Results Strengthening existing human resources Cooperation and division of tasks in business management. Marketing has reached a wider audience by participating in exhibitions and online marketing through Shopee. Permasalahan kerajinan rumah tangga (home industry) pada umumnya adalah produksi, sumber daya manusia dan pemasaran. Mitra Brongkol craft yang merupakan kelompok usaha Ibu-ibu di Dusun Tabaggunung Desa Brongkol Kecamatan Jambu, Kabupaten Semarang Jawa Tengah yang berdiri tahun 2019 juga mengalami hal yang sama. Kondisi pandemic memperburuk kondisi usaha tersebut. Tujuan pengabdian ini adalah meningkatkan omzet penjualan Brongkol Craft melalui pengembangan dan pembenahan aspek produksi, SDM, dan pemasarannya. Metode pemecahan masalah secara umum dilakukan secara partisipatif, pelatihan, pendampingan, monitoring, dan evaluasi di lokasi mitra Brongkol Craft. Pelatihan diimplementasikan dalam bentuk tutorial, diskusi, peragaan, dan praktik. Mitra Brongkol Craft berpartisipasi aktif mengikuti semua aktivitas dalam pelaksanaan kegiatan ini. Setiap tahap kegiatan dimonitor dan dievaluasi pada aspek-aspek partisipasi, pengetahuan, ketrampilan dalam implementasi alih iptek, sikap, dan luaran pada setiap aktivitas kegiatan. Hasil pengabdian masyarakat berupa pengembangan produk Brongkol craft yaitu totebag, sarung bantal, taplak meja, topi dan asesoris lainnya yang berbasis limbah. Hasil Penguatan sumber daya manusia sudah ada Kerjasama dan pembagian tugas dalam Manajemen usaha. Pemasaran sudah menjangkau konsumen lebih luas dengan mengikuti pameran dan pemasaran online melalui Shopee.